A Learning System Design Based on Digital Technology Utilization - Lianly Rompis (SISFORMA, 2018)
Digital technology in Indonesia, especially in Manado, begin to grow very rapidly followed by the availability of adequate technology market, better financial economy, and high enthusiasm from the local people, mostly academic educators. Supported by the existence of network based technology, it is mostly expected that the process of transferring information and learning in classroom will be easier and no longer become great problem in the future. People will acceptdigital technology not as a threat, but cultivate and utilize them for the improvement of human civilization, while keep maintaining respect to traditional learning and manual opinions and analysis because after all those concepts are merely the best. This paper based on author experience, observations, and reviews, offers solutions to utilize digital technology for developing aneffective learning process. The research methods are literature study, analysis taken from personal experience, system design, and future implementation. The results of this research givesperspective to design a learning system in a proper way, using digital technology individually or integrated, which will also support research activities and improve good digital technology products designed and produced by people of Indonesia and other Nations.